DAYA HAMBAT PROPOLIS TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli - Arum Lintang Dyah Lestari; Noverita; Atna Permana (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The increase in diseases caused by bacteria followed by an increase in bacterial resistance to synthetic antibiotics has prompted research on alternative antibacterial producing drugs. Propolis is one of the components of honey, which is an adhesive substance collected by worker bees from shoots, twigs and leaves that produce sap. propolis is known to contain bacteriostatic, bactericidal, fungistatic, and fungicidal antimicrobial compounds. Propolis contains a number of compounds such as resins, flavonoids, phenols, waxes, fatty acids, essential oils, pollen, minerals and vitamins.This study aims to determine the effect of propolis on the growth of Staphylococcus aureus and Escherichia coli bacteria at different concentrations. Antibacterial activity testing was carried out by the agar diffusion test method according to Kirby - Bauer by observing the inhibition zone of the growth of the tested bacteria as a parameter. The research design used was factorial completely randomized design (CRD). The results showed that there was an effect of treatment on the growth of S. aureus bacteria colonies with the best concentration value of 90%, while the E. coli bacterial colonies did not show the effect of concentration treatment on the growth of these bacterial colonies. based on statistical tests using the LSD test for the effectiveness of propolis concentrations in E. coli bacteria showed that propolis with a concentration of 10% was not significantly different from the concentrations of 30%, 50%, 70% and 90%. whereas the LSD test for the effectiveness of propolis concentration in S.aureus bacteria showed that the propolis concentration of 10% was not significantly different from the propolis concentration of 30%, but significantly different from the propolis concentration of 50%, 70% and 90%. Keywords: antibiotic, Escherichia coli, propolis, Staphylococcus aureus